La discriminación laboral vulnera los derechos fundamentales de las personas con discapacidad - Ruiz Soto, Sandra Jacqueline (2015)
The evolution of the social consideration of the discapacitados has gone improving as for its adaptation and, mainly, to its perception. From principles of the decade of the 80 social models of discapacidad have been developed that they add new appreciations and they offer better opportunities of people's discapacitadas insert in the productive society. giving us as a result final that for the factor education has primary studies, 65% secondary 25% and 10% superior level of studies, for the factor employment 67% doesn't either work in public or private institutions and 33% if they have a labor stable source. To determine these percentages or levels, initially he/she thought about to work on two phases, the first of investigation that allows us to know on laws and regulations of our country, city that they include or be related with people that have discapacidad